(untitled) (Media Kesehatan Masyarakat Indonesia, 2019)
Doctor is one of professionals who have an important role in the hospital services. Perception of doctor related organizational support can build doctor’s trust and performance in hospitals. This study aims to analyze the relationship of Perceived Organizational Support (POS) on doctor performance in Class B General Hospital of Makassar City. This research is an observational analytic study with cross sectional design. The total sample in this study was 126 respondents selected by simple random sampling technique. Data were analyzed using Pearson correlation test. The results showed that there was a relationship between perceived organizational support and doctor performance with a p value of 0,010 < 0,05. POS has a relationship to the performance of doctors so hospitals need to increase the involvement of doctors by creating a supportive work environment and creating an innovation program to increase doctors’ trust in the hospital.